2017
DOI: 10.15406/icpjl.2017.04.00107
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neutrophil CD64 as an Emerging Biomarker in the Evaluation of Neonatal Sepsis

Abstract: Background: Early diagnosis and treatment of neonatal sepsis may be helpful in decreasing neonatal mortality. Neonatal sepsis is considered as one of the major causes of morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, the opposite was documented by Paul et al,[13] EOS was observed more (65%) than LOS (35%). https://ejmr.journals.ekb.eg/ consistent with those of Halil et al's[17] study on septic neonates in Turkey, which https://ejmr.journals.ekb.eg/…”
mentioning
confidence: 69%
“…However, the opposite was documented by Paul et al,[13] EOS was observed more (65%) than LOS (35%). https://ejmr.journals.ekb.eg/ consistent with those of Halil et al's[17] study on septic neonates in Turkey, which https://ejmr.journals.ekb.eg/…”
mentioning
confidence: 69%